Data Science for Cyber-Security - Heard,N; Adams,N; Rubin-Delanchy,P (Wspc (Europe), 2018)
This book provides insight into a range of data science techniques for addressing these pressing concerns.The application of statistical and broader data science techniques provides an exciting growth area in the design of cyber defences.